Evaluation of validity of scoring systems in diagnosing acute appendicitis: a single centre prospective observational study - Natesan S., Rakesh; Kumar A., Naren (International Surgery Journal, 2021)
Background: Acute appendicitis is a very common cause of acute abdominal pain, requiring surgical intervention with a 7% life time risk. Various clinical scoring systems like Alvarado, appendicitis inflammatory response (AIR), Tzanaki scores enables risk stratification. In this study, we have validated the diagnostic accuracy of various scoring systems like Alvarado, Tzanaki and AIR scores. Methods: We conducted a prospective observational study for patients admitted in a tertiary care hospital. A total of 81 patients were selected based on the inclusion and exclusion criteria. A detailed clinical history, physical examination, relevant blood investigations and necessary imaging were done for all the patients. Using the above data, the probability of acute appendicitis is calculated using the Alvarado, Tzanaki and AIR scores. The various scores obtained were compared with the histopathological examination (HPE) reports (reference standard) and values like sensitivity, specificity, positive and negative predictive values (PPV and NPV) were calculated. Results: With regard to scores, Alvarado scores has a sensitivity 95.24%, specificity 77.78%, PPV of 93.75%, NPV of 82.35%. Tzanaki score has a sensitivity of 100%, specificity 23.5%, PPV of 83.12% and NPV of 100%. AIR score has a sensitivity of 95%, specificity of 66.67%, PPV of 89.06% and NPV of 82.35%. Conclusions: Alvarado score (cut off 7) has the best PPV (93.75%) and hence is the best scoring system to “rule in” a positive diagnosis. However, Tzanaki score (cut off 8) has the best NPV (100%) and hence is the best score to “rule out” a diagnosis of acute appendicitis.